Effects of Self-Compassion Training on Work-Related Well-Being: A Systematic Review - Kotera, Yasuhiro; Van Gordon, William (Frontiers in Psychology, 2021)
Self-compassion, sharing some commonalities with positive psychology 2.0 approaches, is associated with better mental health outcomes in diverse populations, including workers. Due to the COVID-19 pandemic, there is heightened awareness of the importance of self-care for fostering mental health at work. However, evidence regarding the applications of self-compassion interventions in work-related contexts has not been systematically reviewed to date. Therefore, this systematic review aimed to synthesize and evaluate the utility of self-compassion interventions targeting work-related wellbeing, as well as assess the methodological quality of relevant studies. Eligible articles were identified from research databases including ProQuest, PsycINFO, Science Direct, and Google Scholar. The quality of non-randomized trials and randomized controlled trials (RCTs) was assessed using the Newcastle-Ottawa Scale and the Quality Assessment Table, respectively. The literature search yielded 3,387 titles from which ten studies met the inclusion criteria. All ten studies reported promising effects of self-compassion training for work-related wellbeing. The methodological quality of these studies was medium. All ten studies recruited workers in a caring field and were mostly conducted in Western countries. The Self-Compassion Scale (SCS) or its short-form was used in almost all instances. Findings indicate that self-compassion training can improve self-compassion and other work-related wellbeing outcomes in working populations. However, in general, there is need for greater methodological quality in work-related self-compassion intervention studies to advance understanding regarding the applications and limitations of this technique in work contexts. Furthermore, future studies should focus on a broader range of employee groups, including non-caring professions as well as individuals working in non-Western countries.